Inappropriate restriction of dietary gluten and associated bone acquisition and bone density in Egyptian children with coeliac disease - ElBaky, Abeer Abd; Ismail, Nagwa; Salama, Emad; Abou-Zekri, Maha; Fatouh, Amany; Ragab, Shadia (Archives of Medical Science, 2009)
Introduction: Early onset osteoporosis is a serious complication for coeliac disease (CD). Adherence to a gluten-free diet (GFD) has been shown to restore bone density. The aim of the study was to evaluate the association between inappropriate dietary restriction of gluten and bone density in children with CD. Material and methods: Twenty-one children with CD were diagnosed according to guidelines of the North American Society of Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN). All patients had persistent high level of anti-tissue transglutaminase IgA antibody (IgA-tTG). Ten males and 11 females, mean age 7.52 ±4.19 years. Thirty healthy children were included as controls. Laboratory investigation included serum osteocalcin, carboxy-terminal propeptide of type I collagen (CICP), osteoprotegerin and receptor activator of nuclear factor kB (RANKL) and urinary deoxypyridinoline (DPD). Bone mineral density and content (BMD and BMC) were measured by dual X-ray absorptiometry (DEXA) in spinal lumbar and femoral neck regions. Results: Spinal lumbar BMD and BMC, and femoral BMD and BMC were significantly lower in patients than controls (p = 0.007, 0.003 respectively) (p = 0.002, 0.006 respectively). There were statistically significant decreases in serum calcium, osteocalcin, CICP and osteoprotegerin levels in patients compared to controls (p = 0.0002, 0.0001, 0.01 and 0.0001 respectively). Conclusions: Egyptian children with CD not adherent to GFD had BMD and BMC values significantly lower than in controls. These results emphasize that compliance to GFD is the main challenge for the patients and physicians.